Platelet aggregation, dyslipoproteinemia and polyunsaturated fatty acids - E. I. Sokolov; V. A. Metelskaya; N. V. Perova; G. N. Shchukina; V. M. Fomina (Кардиоваскулярная терапия и профилактика, 2006)
The article reviews the trials on the association between increased functional activity of platelets and platelet membrane polyunsaturated fatty acids (PUFA), PUFA in serum lipoprotein phospholipids, and dyslipoproteinemia (DLP) type and severity. Platelet structural and functional disturbances, often accompanying DLP and influenced by its type, affect platelet aggregation – via platelet membrane lipid modification, as well as via modified synthesis of platelet functional activity modulators (e.g., TxA2 ). Possible approaches to platelet hyperaggregation correction are discussed, including membrane lipid modulation via lipoprotein profile normalization during pharmaceutical and non-pharmaceutical treatment.